Flexible response and rapid recovery strategies of the plateau forage Poa crymophila to cold and drought - Li, Xin-Yu; Wang, Yan; Hou, Xin-Yi; Chen, Yan; Li, Cai-Xia; Ma, Xin-Rong (Frontiers in Plant Science, 2022)
Cold and drought stress are the two most severe abiotic stresses in alpine regions. Poa crymophila is widely grown in the Qinghai–Tibet Plateau with strong tolerance. Here, by profiling gene expression patterns and metabolomics-associated transcriptomics co-expression network, the acclimation of Poa crymophila to the two stresses was characterized. (1) The genes and metabolites with stress tolerance were induced by cold and drought, while those related with growth were inhibited, and most of them were restored faster after stresses disappeared. In particular, the genes for the photosynthesis system had strong resilience. (2) Additionally, cold and drought activated hypoxia and UV-B adaptation genes, indicating long-term life on the plateau could produce special adaptations. (3) Phenolamines, polyamines, and amino acids, especially N′,N″,N′″-p-coumaroyl-cinnamoyl-caffeoyl spermidine, putrescine, and arginine, play key roles in harsh environments. Flexible response and quick recovery are strategies for adaptation to drought and cold in P. crymophila, accounting for its robust tolerance and resilience. In this study, we presented a comprehensive stress response profile of P. crymophila and provided many candidate genes or metabolites for future forage improvement.